Taro production, phytomass input by Sesbania and Flemingia and improvement in soil fertility in agroforestry systems in floodplains - Devide, Antonio Carlos Pries; Ribeiro, Raul de Lucena Duarte; Abboud, Antônio Carlos de Souza; Castro, Cristina Maria de; Pereira, Marcos Gervasio (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
Floodplains were the first deforested areas for agriculture use all over the world. In Brazil these areas can be restored by the growth of guanandi Calophyllum brasiliense, a slow-growing native forest species adapted to flooding. The aims of this study were to: (i) evaluate the taro, Colocasia esculenta, management under two agroforestry systems (AFS) (Simple and Biodiverse) in succession to a reforestation with guanandi, (ii) evaluate the contribution of macronutrients from the green manure Flemingia macrophylla and Sesbania virgata, both managed using pruning for green manure in the respective AFSs, and (iii) the effects on soil nutrients levels compared to monoculture of guanandi (control). The randomized block was designed with eight replication and 216.0 m² plots with four rows of six guanandi trees in each line. In the simple AFS (SAFS), the taro was intercropped with Flemingia and in the biodiverse AFS (BAFS), Sesbania, banana shrub (Musa sp.), edible palm (Euterpe edulis) and fourteen species of native trees were included. Production was evaluated in seasons with high rainfall and water scarcity. With floods the taro has produced around 15 Mg ha-1 of marketable corms in the SAFS and 9 Mg ha-1 in the BAFS, but the drought has made commercial production unfeasible, with no differences between cormels and corms planting. However, enough rhizomes were harvested for a new planting. Flemingia has accumulated 17 Mg ha-1 of fresh matter and Sesbania contributed with 2 Mg ha-1. Soil pH and macronutrient content, especially K, were significantly higher in AFSs areas compared to guanandi monoculture.